VD_FINDINFO HC / 2012 / 610 vom 20. September 2012 - VD Tribunal cantonal (2012)
CUMUL D'ACTIONS, BAIL À LOYER, COMPÉTENCE RATIONE MATERIAE | 257d CO, 243 al. 2 let. c CPC (CH), 90 CPC (CH), 1 al. 3 LJB